ARITHMATOPIA: USING MOBA GAME TO INCREASE BASIC CALCULATION PROFICIENCY - Fithratu Al Laili, Chalimi
This study aims to determine whether playing Arithmatopia, a MOBA game that applies gamification of the number bonds as one of the basic mathematics learning method, can improve the fluency of basic math calculations, especially single digit numbers. This game also implements the Teams-Games-Tournaments learning method as the foundation for the competitive and cooperative learning components. The researcher used a quasi-experimental design with pre-test and post-test to measure the level of fluency of the students in completing the one-digit number addition exercises. We test two groups of first graders of primary school. One group plays the Arithmatopia game and the other group does not. Both groups were taught by the same math teacher. At the end of the study, we found that the two groups showed significant differences between the pre-test and post-test. Statistically using the one-way ANOVA test, the group that played Arithmatopia had a higher average score improvement than the other groups that didn't play